IDN-Laser-Tester: A Framework for Detecting and Testing ILDA Digital Network Consumers for Laser Projection - Frank, Matthias (Electronic Communications of the EASST, 2021)
The ILDA Digital Network (IDN) is a novel protocol family providing digital data transmission for laser projection. While the new standards mainly aim to replace the old analogue signal transmission, the digital streaming concept also enables completely new applications and flexible networked scenarios. Very simple tools are existing to check the old analogue connection. Our demo presents the IDN-Laser-Tester, a new framework that allows for detecting and testing IDN enabled hardware or software in a local network in a user friendly manner from smartphone, tablet or portable computer.